Misuse, Abuse, and Dependence of Over-the-Counter Medicines: A Systematic Review - Ganjala, Hemalatha; Nakka, Anusha; Prathi, Mary Asha; Padigala, Ramya Jyothi; Gajula, Ram Nageswara Rao; Ravipudi, Sravan Kumar; Chakka, Umakirthi; Dimmiti, Jayasri; Shaik, Faizan Ali (Journal of Pharmacy Practice and Community Medicine, 2026)
Background Over-the-Counter (OTC) medicines are commonly used for the management of minor illnesses and are easily available without a prescription. Although these medicines are considered safe when used correctly, inappropriate use, misuse, and dependence are increasingly being reported worldwide. Objectives The present study aimed to systematically review the published literature regarding the patterns, causes, and health consequences of OTC medicine misuse, abuse, and dependence. Materials and Methods A systematic search was conducted in PubMed, Scopus, Web of Science and Cochrane Library for studies published between January 2014 and December 2024. Observational and survey-based studies involving human participants that reported misuse or dependence on OTC medicines were included. Titles and abstracts were screened, followed by full-text assessment for eligibility. Data were extracted from the selected studies and summarized qualitatively according to PRISMA guidelines. The review was conducted and reported according to PRISMA 2020 guidelines. Results A total of 33 studies met the inclusion criteria. Analgesics and non-steroidal anti-inflammatory drugs were the most frequently reported medicines, followed by codeine-containing products, cough suppressants, antihistamines, and antidiarrheal agents. Common reasons for misuse included easy accessibility, self-medication practices, and lack of awareness regarding adverse effects. Reported complications included hepatotoxicity, gastrointestinal irritation, cardiovascular effects, and drug dependence. Conclusion OTC medicine misuse represents an important public health concern. Increasing public awareness, appropriate pharmacist counseling, and better monitoring of high-risk OTC medicines are necessary to promote safe use and prevent associated health complications.
Keywords: Abuse; Dependence; Misuse; Over-the-counter drugs; Self-medication; Systematic review